Perancangan Operasi Optimal Pembangkit Listrik Tenaga Diesel (PLTD) Dan Pembangkit Listrik Tenaga Biogas (PLTBiogas) Di Kabupaten Kepulauan Meranti Menggunakan Metode Economic Dispatch - Martha Dewa; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Utilization of renewable energy sources and conversion devices increasingly varied. Sago waste as a source of cleanliness issues, can be viewed as a source of alternative energy with green technologies both of process and product. Construction of biogas power plant (PLTBiogas) is a solution of renewable energy (EBT) to increase energy needs and help to reduce dependence on fuels (fossil energy). To reduce the cost of fuel, optimalize schedule of thermal generating units in the system need to be done . Problem related to the schedule is the Economic Dispatch consists of dividing the load at each generating unit in order to obtain a combination of generating units to meet the load demand with optimum. Dividing of cost of load for each thermal generating unit can be obtained by using the lambda iteration method. This methode can achieve more optimal results .Keywords: Construction of biogas power plant (PLTBiogas), Economic Dispatch, Lamda iteration